2008
DOI: 10.1093/rpd/ncn185
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distributions and gamma dose rates of 40K, 232Th, 238U and 137Cs in the selected forest soils in Izmir, Turkey

Abstract: This paper presents the results obtained from a radioecological study carried out in the selected forest sites of Izmir, Turkey. The levels of gamma-emitting radionuclides, 40K, 232Th, 238U and 137Cs, in soils were determined using gamma spectroscopy. The activity profile for 40K, 232Th and 238U exhibits a uniform distribution with respect to depth. The depth distribution of 137Cs activity was established by fitting the experimental points to an exponential or a Gaussian function. About 42-97% of the 137Cs dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The maximum mass activity of 40 K, 724 Bq kg À1 , was measured in the 30e40 cm soil increment. Generally, the vertical distribution of 40 K in soil is uniform (Karadeniz and Yaprak, 2008). However, our mass activity results suggest that potassium distribution in natural soils is not always homogenously distributed.…”
Section: Baseline Level Of Nors Activity and Physicochemical Elementsmentioning
confidence: 61%
“…The maximum mass activity of 40 K, 724 Bq kg À1 , was measured in the 30e40 cm soil increment. Generally, the vertical distribution of 40 K in soil is uniform (Karadeniz and Yaprak, 2008). However, our mass activity results suggest that potassium distribution in natural soils is not always homogenously distributed.…”
Section: Baseline Level Of Nors Activity and Physicochemical Elementsmentioning
confidence: 61%
“…40 The specific activities of 137 Cs were maximal at 10-15 cm depth, which is in accordance with numerous studies showing that 137 Cs deposition is mostly contained within the surface soil layer. [41][42][43] The 137 Cs specific activities in the surface soil layers showed a wide range of values (from 8.3 to 160 Bq kg À1 in the 0-5 cm layer and from 8.4 to 120 Bq kg À1 in the 5-10 cm layer), which could be attributed to non-homogeneous surface contamination after the Chernobyl accident. The 137 Cs inventories calculated according to eqn (1) were found to vary between 60 Bq m À2 for profile C and 320 Bq m À2 for profile E, which is in accordance with values reported for Belgrade area after the Chernobyl accident.…”
Section: Distribution Of Natural Radionuclides and 137 Cs In Soilsmentioning
confidence: 99%
“…Numerous studies following the Chernobyl accident have shown that soil is the main reservoir for radiocesium [1][2][3] and its spatial distribution in soil has been widely investigated. [4][5][6] It has been recognized that 137 Cs was mostly deposited in the surface soil layer (0-15 cm) [7][8][9] and that its concentration decreases slightly with depth. [10][11][12][13] The physicochemical characteristics of soil and other environmental conditions inuence the migratory behavior of cesium in soil.…”
Section: Introductionmentioning
confidence: 99%